The Attitudes of Chinese Organizations Towards Cloud Computing: An Exploratory Study - Issa, Theodora; Issa, Tomayess; Duan, Yuchao; Chang, Vanessa (2016)
Cloud Computing become a significant factor in E-commerce and E-business processes and will reduce negative IT impacts on the environment without compromising the needs of future generations. This chapter aim to examine the attitudes of Chinese Organizations towards Cloud Computing adoption. This chapter provides an answer to the question: “What are the advantages and disadvantages of Cloud Computing adoption in Chinese organizations?” The answer was sought by means of an online survey of (N=121) respondents. The survey results revealed the Chinese position regarding the cloud movement, its strengths and weaknesses, the threats posed by Cloud Computing in China, and the specific advantages and disadvantages of this new technology that Chinese organizations and research communities should embrace for the realization of future cloud systems.